Effect of Circuit Training on Physical Fitness of the School Softball Players - Hanotiya, Ajay; Saxena, Vikas (Journal for Research in Applied Sciences and Biotechnology, 2023)
The purpose of this study was to investigate the effect of circuit training on the physical fitness of the school's softball players. Twenty (20) subjects were selected for the study; their ages were 18–19. They attended St. Joseph convent school in Namli Ratlam, M.P. Further, it is subdivided into two groups. Three variables were selected for this study to measure the physical fitness of schoolgirls’ softball fitness, i.e., standing broad jump, sit and reach, and 50-metre sprint. The data was examined by applying the analysis of paired t-tests. The level of significance to test the hypothesis was set at 0.05. Results of this study revealed that there was a significant effect of circuit training on the physical fitness of the school softball players and that it increased their performance at the school level.